The silent mutational landscape of infant MLL‐AF4 pro‐B acute lymphoblastic leukemia. Issue 10 (26th July 2013) - Dobbins, Sara E.; Sherborne, Amy L.; Ma, Yussanne P.; Bardini, Michela; Biondi, Andrea; Cazzaniga, Giovanni; Lloyd, Amy; Chubb, Daniel; Greaves, Mel F.; Houlston, Richard S.
<x xml:space="preserve">Abstract</x> Over 90% of infants (<1‐year‐old) diagnosed with leukemia have pro‐B acute lymphoblastic leukemia (ALL) containing the MLL‐AF4 fusion. When compared with other forms of paediatric ALL affecting later B‐cell differentiation, MLL‐AF4 pro‐B is associated with a dismal prognosis with a typical 5‐year disease‐free survival of <20%. MLL‐AF4 may be sufficient on its own for leukemogenesis or the gene‐fusion product may alternatively predispose transformed cells to global genetic instability, enhancing the acquisition of additional key mutations. To gain insight into the genomic landscape of infant MLL‐AF4 pro‐B ALL we performed whole genome sequencing of diagnostic leukemic blasts and matched germline samples from three MLL‐AF4 pro‐B ALL infants. Our analysis revealed few somatic changes (copy number abnormalities, loss of heterozygosity, or single nucleotide variants), demonstrating that only a very small number of mutations are necessary to generate infant MLL‐leukemia. © 2013 Wiley Periodicals, Inc.